2021
DOI: 10.3389/fimmu.2021.693974
|View full text |Cite
|
Sign up to set email alerts
|

CLEC-2 Prevents Accumulation and Retention of Inflammatory Macrophages During Murine Peritonitis

Abstract: Platelets play a key role in the development, progression and resolution of the inflammatory response during sterile inflammation and infection, although the mechanism is not well understood. Here we show that platelet CLEC-2 reduces tissue inflammation by regulating inflammatory macrophage activation and trafficking from the inflamed tissues. The immune regulatory function of CLEC-2 depends on the expression of its ligand, podoplanin, upregulated on inflammatory macrophages and is independent of platelet acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…98,99 Beside its prothrombotic role, CLEC-2-podoplanin interaction has also been implicated in acute respiratory distress syndrome (ARDS), sepsis and peritoinitis in mice. [100][101][102] Such findings suggest the therapeutic potential of targeting CLEC-2 and GPVI interactions to regulate thrombosis and thromboinflammation. Emerging research during the current COVID-19 pandemic has revealed that COVID-19 patients have hyperactive and procoagulant platelets, as well as platelet-leukocyte aggregates characteristic of thr omboinflammation.…”
Section: The Binding Between Platelet P-selectin With P-selectin Glyc...mentioning
confidence: 94%
See 1 more Smart Citation
“…98,99 Beside its prothrombotic role, CLEC-2-podoplanin interaction has also been implicated in acute respiratory distress syndrome (ARDS), sepsis and peritoinitis in mice. [100][101][102] Such findings suggest the therapeutic potential of targeting CLEC-2 and GPVI interactions to regulate thrombosis and thromboinflammation. Emerging research during the current COVID-19 pandemic has revealed that COVID-19 patients have hyperactive and procoagulant platelets, as well as platelet-leukocyte aggregates characteristic of thr omboinflammation.…”
Section: The Binding Between Platelet P-selectin With P-selectin Glyc...mentioning
confidence: 94%
“…Recently, platelet ITAM receptors C‐type lectin‐like receptor 2 (CLEC‐2) and GPVI have emerged as novel targets in thromboinflammatory diseases, due to the finding that CLEC‐2 interaction with its ligand podoplanin promotes venous thrombosis 98,99 . Beside its prothrombotic role, CLEC‐2‐podoplanin interaction has also been implicated in acute respiratory distress syndrome (ARDS), sepsis and peritoinitis in mice 100–102 . Such findings suggest the therapeutic potential of targeting CLEC‐2 and GPVI interactions to regulate thrombosis and thromboinflammation.…”
Section: Nanomedicine Inspired By Platelet Role In Thrombosis and Thr...mentioning
confidence: 99%
“… 36 Moreover, Bourne et al reported that crosslinking podoplanin using recombinant CLEC-2-Fc limited the inflammatory environment by reducing inflammatory macrophage accumulation in the inflamed tissue during murine peritonitis. 37 Platelet CLEC-2 induces a loss of phosphorylation of the serine residues in the intracellular podoplanin tail, which is associated with a rapid translocation of podoplanin from intracellular stores to the surface of inflammatory macrophages. 38 Additionally, the interaction between podoplanin and CLEC-2 induced the reorganisation of the actin cytoskeleton and increased podoplanin interaction with ERM proteins and CD44, promoting macrophage migration.…”
Section: Podoplanin Expression In the Innate And Adaptive Immune Systemsmentioning
confidence: 99%
“… 38 Additionally, the interaction between podoplanin and CLEC-2 induced the reorganisation of the actin cytoskeleton and increased podoplanin interaction with ERM proteins and CD44, promoting macrophage migration. 37 Cheok et al also proposed that during Helicobacter pylori infection, podoplanin drives motility of active macrophages via regulating Filamin C, a member of actin-crosslinking protein family that stabilizes and links actin web to the cell membrane. 39 , 40 They demonstrated that podoplanin may promote Filamin C transactivation through interacting with the ERM complex and activating Rho GTPase signaling pathway, but further investigation is required to confirm this notion.…”
Section: Podoplanin Expression In the Innate And Adaptive Immune Systemsmentioning
confidence: 99%
“…It has been reported that the CLEC2-PDPN axis can regulate cell contractility and migration through activation of ERM proteins in non-cancerous settings ( 153 155 ). In this regard, it is plausible that the PDPN-ERM axis could be recruited by tumors bound to platelets via CLEC2-PDPN interaction, conferring cancer cells metastatic potentials ( Figure 1 ).…”
Section: Interaction Between Platelets and Cancer: Clec2-pdpn-erm Axismentioning
confidence: 99%